2017
DOI: 10.1515/pesd-2017-0030
|View full text |Cite
|
Sign up to set email alerts
|

2006-2012 Land Cover and Use Changes in Romania – An Overall Assessment Based on Corine Data

Abstract: Abstract. Land cover and use changes are an important component of the global changes, and in relationship with their transitional dynamics reflect the impact of socio-economic transition. This study is aimed at exploring the land cover and use changes occurred during 2006-2012 in Romania with respect to their spatial distribution over the regions of development and main transitional dynamics. The results suggest that the main drivers of change are deforestation and urbanization, accounting for 3/4 of all chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Different studies indicated that the Romanian natural protected areas cover preferentially critical areas, such as the mountains (Petrişor and Petrişor, 2017a) and wetlands (Petrişor, 2010). However, the protection status was not always enforced (Petrişor, 2018)…”
Section: Introductionmentioning
confidence: 99%
“…Different studies indicated that the Romanian natural protected areas cover preferentially critical areas, such as the mountains (Petrişor and Petrişor, 2017a) and wetlands (Petrişor, 2010). However, the protection status was not always enforced (Petrişor, 2018)…”
Section: Introductionmentioning
confidence: 99%
“…Protecting and monitoring the evolution of forest areas is an international concern that is reflected in different monitoring programs or methods and techniques that are necessary taking into account the effects of these practices [13]. Of all the methods for analyzing and measuring forest surfaces, satellite imaging and GIS methods have proven to be the most efficient and efficient [14], [15], [16], [17], [18], [19]. Romania is one of the European countries that has natural virgin forests but also many protected areas that are part of the European national program Natura2000, areas which are mainly in mountain areas such as the Apuseni Mountains [20], [21].…”
Section: Introductionmentioning
confidence: 99%
“…At both global and European Union level, the protection and monitoring of the evolution of forest areas has become an important objective [14], which is necessary in the context presented previously. The most efficient way to track the spatial and temporal evolution of the forest fund is by using remote sensing and GIS by providing and interpreting satellite images [15], [16], [17], [18], [19]. Globally, this is done by the FAO (Food and Agriculture Organization of the United Nations) through its Forest Resources Assessment (FRA-FAO) report, which also monitors the evolution of forest areas through a Global Remote Sensing Survey (RSS), the purpose of which is to observe the forested and deforested areas [20].…”
Section: Introductionmentioning
confidence: 99%